Longitudinal Treatment Patterns of Chorea in North American Patients with Huntington’s Disease: Data from Enroll-HD - Erin Furr Stimming; Daniel O. Claassen; Ginny P. Sen; Olga Klepitskaya; Michael Serbin; Hyunwoo Kim; Sean C. Hinton; Dietrich Haubenberger (Neurology and Therapy)
Abstract Introduction Chorea is the primary manifestation of Huntington’s disease. Different clinicians pursue varied approaches to chorea management, and real-world evidence describing them is needed. The objective of this study was to assess the presence and severity of chorea, chorea pharmacotherapy, and treatment practice, and patterns in a large natural-history cohort with Huntington’s disease. Methods The Enroll-HD research platform Periodic Dataset 5.0 was used to select subjects. Outcomes included demographics, disease-related baseline characteristics (Primary Analysis Set), and treatment patterns (Treatment Analysis Set). Results A total of 2590 manifest participants comprised the Primary Analysis Set with 1040 in the Treatment Analysis Set; 96.8% of participants had chorea. Mean Unified Huntington’s Disease Rating Scale scores for Total Maximal Chorea, Total Motor Score, and Total Functional Capacity were 9.6, 39.5, and 7.8, respectively. During the observation period from June 2012 to October 2020, 906 (36.1%) participants received treatment for chorea. Among these, the most common first-line therapies were monotherapy VMAT2 inhibitors (49.9%) and antipsychotics (27.7%), while 7.8% of participants discontinued first-line therapy. Of those receiving VMAT2 inhibitors or antipsychotics as first line, 92% and 84%, respectively, remained on VMAT2 inhibitors or antipsychotics alone or in combination for the duration of the study. The most common second-line treatment was combination therapy. Conclusions Only 36.1% of participants with chorea were taking a medication indicated for chorea, and, while 49.9% of treated participants received VMAT2 inhibitors first-line, approximately half were prescribed off-label alternatives. It is unclear why patients with indications for treatment were untreated or why off-label alternatives were prescribed. Future research should elaborate on these observations.